An Empirical Glimpse on MSEs Four MENA Countries - Weshah Razzak (Economics and Econometrics Research Institute (EERI), 2009)
The Economic Research Forum (ERF) produced a one-off survey of micro & small private enterprises (MSE) in a number of Middle East and North African countries (MENA). It contains sufficient information to fit a production function and additional information about the owner's education type; the scope of the market; and the type of technology. Further, it provides information about perceived constraints to production. We test the effect of these factors on technical progress. We believe that empirical research of policy issues can help promote the making of `evidence-based policies' in the MENA countries.
Keywords: C13; C21; D24; 330; Micro-small private enterprise; production function; stochastic dominance